The influence mechanism of outward FDI reverse technology spillovers on China’s green innovation - Qin, Bingtao; Gao, Yaqi; Ge, Liming; Zhu, Jialing (Technological and Economic Development of Economy, 2023)
With rapid global development, outward foreign direct investment (FDI) has become a controversial issue, mainly focused on whether it is helpful to domestic green innovation, especially in developing countries. How does outward FDI reverse spillover technology to China, and does China’s innate endowment restrict it? The relevant mechanisms remain unclear. Therefore, this study investigated the heterogeneous effect of absorptive capacity on the impact path of reverse technology spillovers of outward FDI on green innovation in China. A fixed-effects panel model and stepwise regression analyze the direct relationship between outward FDI and green innovation and the mediating relationship of absorptive capacity. Threshold analysis reveals the mutation point of the mediating effect of absorptive capacity among China’s 31 provinces. Domestic green innovation is directly stimulated by more significant reverse technology spillovers of outward FDI. Absorptive capacity has an indirect impact as an intervening variable. The mediating effect will only make sense on one side of the threshold because the transformation effectiveness of green innovation is improved only by greater absorptive capacity, including adequate green financial support, more outstanding human capital, and a smaller technology gap. Moreover, it revealed significant regional heterogeneity in China. First published online 01 December 2022